Impact of a ketogenic diet on metabolic parameters in patients with obesity or overweight and with or without type 2 diabetes: A meta-analysis of randomized controlled trials - Choi, Yeo Jin; Jeon, Sang Min; Shin, Sooyoung (Nutrients, 2020)
The aim of this meta-analysis was to explore the efficacy of a ketogenic diet in metabolic control in patients with overweight or obesity and with or without type 2 diabetes. Embase, PubMed, and Cochrane Library were searched for randomized controlled trials that enrolled patients with overweight or obesity on a ketogenic diet for metabolic control. Fourteen studies were included in meta-analysis. The effects of ketogenic diets on glycemic control were greater for diabetic patients relative to those of low-fat diets, indicated by lower glycated hemoglobin (SMD, −0.62; p < 0.001) and homeostatic model assessment index (SMD, −0.29; p = 0.02), while comparable effects were observed for nondiabetic patients. Ketogenic diets led to substantial weight reduction (SMD, −0.46; p = 0.04) irrespective of patients’ diabetes status at baseline and improved lipid profiles in terms of lower triglyceride (SMD, −0.45; p = 0.01) and greater high-density lipoprotein (SMD, 0.31; p = 0.005) for diabetic patients. Other risk markers showed no substantial between-group difference post intervention. Our study findings confirmed that ketogenic diets were more effective in improving metabolic parameters associated with glycemic, weight, and lipid controls in patients with overweight or obesity, especially those with preexisting diabetes, as compared to low-fat diets. This effect may contribute to improvements in metabolic dysfunction-related morbidity and mortality in these patient populations.
Keywords: Adolescent; Adult; Aged; Blood Glucose; Body Weight; Diabetes Mellitus, Type 2; Diet, Ketogenic; Female; Humans; Lipids; Male; Middle Aged; Obesity; Overweight; Randomized Controlled Trials as Topic; Young Adult; Glycemic control; Ketogenic diet; Obesity; Type 2 diabetes